High Prevalence of dam and fimA , Biofilm Formation, and Antibiotic Resistance in Uropathogenic Escherichia coli - Rini Purbowati; Sri Lestari Utami; Agusniar Furkani Listyawati (Cell and BioPharmaceutical Institute, 2026)
Background: Urinary tract infections (UTIs) are among the most common bacterial infections in women and remain a significant public health problem. Uropathogenic E. coli (UPEC) is the main cause of UTIs and can form biofilms, which lead to recurrent infections and antibiotic resistance. Type 1 fimbriae in UPEC, encoded by the fim operon, facilitate bladder attachment, while the dam an orphan DNA methyltransferase in E. coli, contributes to bacterial colonization and biofilm formation. Data on the association between antibiotic susceptibility, fimA and dam gene prevalence, and biofilm formation in UPEC isolates from UTI patients in Indonesia remain limited. This study aimed to investigate the association of the dam and fimA virulence genes with biofilm formation in UPEC causing UTIs.Materials and Methods: Fifty UPEC isolates were obtained from a clinical microbiology laboratory. Biofilm formation was assessed using the tube method. Antibiotic susceptibility testing was performed using the Kirby–Bauer disk diffusion method with amoxicillin, ciprofloxacin, and gentamicin. The presence of the dam and fimA was determined by PCR.Results: Seventy percent of UPEC isolates were capable of biofilm formation. High resistance rates were observed for amoxicillin (92%), ciprofloxacin (88%), and gentamicin (56%). In UPEC isolates that were positive for the dam, 62% of them had the ability to form biofilms. Meanwhile, in UPEC isolates that were positive for the fimA, 52% of them had the ability to form biofilms.Conclusion: UPEC isolates showed a high prevalence of the dam and fimA genes, which were associated with biofilm formation and increased antibiotic resistance.Keywords: biofilm, antibiotic, dam, fimA, urinary tract infections